Meta-analysis Comparing Platelet-Rich Plasma vs Hyaluronic Acid Injection in Patients with Knee Osteoarthritis. Issue 7 (7th March 2019) - Han, Yanhong; Huang, Hetao; Pan, Jianke; Lin, Jiongtong; Zeng, Lingfeng; Liang, Guihong; Yang, Weiyi; Liu, Jun
Abstract : As a minimally invasive treatment option, intra-articular injection of platelet-rich plasma (PRP) has been widely used in clinical therapy. Our meta-analysis showed that PRP injections constitute an effective and safe alternative treatment for long-term pain relief and functional improvement in patients with knee osteoarthritis (KOA). The optimal dosage, timing intervals and frequency of injections and the ideal treatment for different stages of KOA remain areas of concern for future investigation future. Abstract: Purpose: The purpose of this meta-analysis was to compare platelet-rich plasma (PRP) and hyaluronic acid (HA) in patients with knee osteoarthritis (KOA). Methods: Randomized controlled trials (RCTs) comparing the use of PRP and HA in KOA patients were retrieved from each database from the establishment date to April 2018. Outcome measurements were the Western Ontario and McMaster Universities Arthritis Index (WOMAC), visual analog scale (VAS), International Knee Documentation Committee, and Lequesne Index scores and adverse events. The pooled data were evaluated with Review Manager 5.3.5. Results: Fifteen RCTs (N = 1, 314) were included in our meta-analysis. The present meta-analysis indicated that PRP injections reduced pain more effectively than HA injections in patients with KOA at six and 12 months of follow-up, as evaluated by the WOMAC pain score; the VAS pain score showed a significant difference at 12 months. Moreover, better functional improvement was observed in the PRP group, as demonstrated by the WOMAC function score at three, six, and 12 months. Additionally, PRP injections did not display different adverse event rates compared with HA injections. Conclusion: In terms of long-term pain relief and functional improvement, PRP injections might be more effective than HA injections as a treatment for KOA. The optimal dosage, the timing interval and frequency of injections, and the ideal treatment for different stages of KOA remain areas of concern for future investigations.